2016
DOI: 10.1007/s00213-016-4386-7
|View full text |Cite
|
Sign up to set email alerts
|

On-the-road driving performance after use of the antihistamines mequitazine and l-mequitazine, alone and with alcohol

Abstract: ObjectivePrevious studies demonstrated that mequitazine produces mild sedation after single doses.Its enantiomer, l-mequitazine, has a stronger potency for the H1 receptor. The aim of the current study was to assess the effects of l-mequitazine and mequitazine, alone and with alcohol, on driving.MethodsTwenty-five healthy volunteers were treated with l-mequitazine 2.5, 5.0 and 10 mg, mequitazine 10 mg and placebo, alone and in combination with alcohol in a double-blind crossover design. Driving performance was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
2
1
0
Order By: Relevance
“… Participants exhibited an increase in SR driving fatigue during the post-DST trial, when considering both objective measurements, i.e., SDLP and PERCLOS. In absolute terms, the increase in fatigue as assessed by SDLP was greater than that previously documented for alcohol and comparable to that previously documented for a hypnotic ( van der Sluiszen et al, 2016 , Vinckenbosch et al, 2020 ); the increase in PERCLOS values was comparable to that of sleep-deprived drivers ( Jackson et al, 2016 ). Both were higher than the increases observed in partially sleep-deprived drivers in the same simulator scenario ( Cellini et al, 2023 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“… Participants exhibited an increase in SR driving fatigue during the post-DST trial, when considering both objective measurements, i.e., SDLP and PERCLOS. In absolute terms, the increase in fatigue as assessed by SDLP was greater than that previously documented for alcohol and comparable to that previously documented for a hypnotic ( van der Sluiszen et al, 2016 , Vinckenbosch et al, 2020 ); the increase in PERCLOS values was comparable to that of sleep-deprived drivers ( Jackson et al, 2016 ). Both were higher than the increases observed in partially sleep-deprived drivers in the same simulator scenario ( Cellini et al, 2023 ).…”
Section: Discussionsupporting
confidence: 85%
“…In absolute terms, the marginal mean of SDLP was 0.256 m in the pre-DST trial and 0.296 m in the post-DST. This 4 cm increase is relevant also under a physical point of view, since, for reference, it is higher than the SDLP increase reported after the administration of 0.5 g/L alcohol (2.6 cm, van der Sluiszen et al, 2016 , Vinckenbosch et al, 2020 ), and comparable to that reported after the administration of 10 mg of the sleep-inducing medication zolpidem (3.8 cm, Vinckenbosch et al, 2020 ). The marginal mean of PERCLOS increased from 4.59% of trial 1 to 5.90% of trial 2, which is comparable to the 1.66% increase observed in drivers performing a similar driving task after 24 h of total sleep deprivation ( Jackson et al, 2016 ).…”
Section: Discussionsupporting
confidence: 49%
“…In order to validate proposed operationalizations of lane drifts (Verster et al, 2014;Verster et al, 2018), data was pooled from 11 randomized, placebo-controlled, cross-over studies that employed the on-the-road driving test and were conducted at two independent research centers. These studies were originally designed to assess the effects of alcohol (Kuypers et al, 2006;van der Sluiszen et al, 2016), hypnotics (Jongen et al, 2018;Mets et al, 2011;Leufkens et al, 2009;Vermeeren et al, 2018;Vermeeren et al, 2016;Vermeeren et al, 2015;Vermeeren et al, 2014;Verster et al, 2002), and sleep deprivation (Jongen et al, 2015) and were selected for the current investigation because the administered treatments were found to significantly affect the SDLP. The pooled dataset included 315 healthy volunteers of both sexes who drove after alcohol (N = 49), zopiclone (N = 194), zolpidem (N = 72), oxazepam (N = 43), diazepam (N = 21) and sleep deprivation (N = 23) and after placebo (N = 315).…”
Section: Methodsmentioning
confidence: 99%